Keris warisan Melayu = Kris, a Malay heritage - Abdul Mua'ti; Muhammad Pauzi Abd. Latiff (Penerbit Universiti Putra Malaysia, 2016)
The keris is a weapon produced by the Malays, the native inhabitants of the Malay World. In addition to being used as a weapon, the kris is also a symbol of honor, power and complementary Malay dress in ceremonial ceremonies. This book is produced to introduce the keris to readers. Thus the book features sections on keris, variations of eyelets, headlines, gloves, and fans. All the keris shown in this book is a collection of Malay Heritage Museum, Universiti Putra Malaysia. This book is written in both Malay and English